Effect of Excipients on Oxcarbazepine Release from Modified Release Matrix Tablets - Buchi N. Nalluri, S. Vidyasagar, K. M. Maheswari (Journal of Applied Pharmaceutical Science)
The present investigation was undertaken with an objective of formulating modified release (MR) matrix tablets of Oxcarbazepine (OXC) an anti-epileptic drug, based on cellulose ether polymers like Hydroxy Propyl Methyl Cellulose (HPMC K4M and LVCR 100) and Hydroxy Propyl Cellulose (HPC JF) as drug release retardants to overcome poor patient compliance and exposure to high doses associated with currently marketed immediate release (IR) dosage forms. The tablets were prepared by direct compression process and evaluated for various physico- chemical/mechanical parameters. Among three polymers used, HPMC LVCR 100 is selected as release retardant based on the viscosity and gel formation during dissolution. The effect of different fillers like Avicel PH 101, Avicel PH 105, Pre gelatinized starch (PGS), maize starch with spray dried lactose (FLOWLAC) and Di-calcium phosphate (DCP) on OXC release was also studied and the OXC percent release at the end of 12h is in the order of DCP>FLOWLAC>Avicel PH 101>Avicel PH 105>PGS. Based on the dissolution data obtained with different fillers and keeping in view of the results from the pre compression studies, and gel layer retaining with the matrix tablets, Avicel PH 105 was selected as carrier to carry out further formulation development. Since, OXC is poorly water soluble drug, solubilizing agents like surfactants, cyclodextrins and polyethylene glycols were included in the formulations and their effect on OXC release was studied in order to achieve therapeutic effective levels. Formulations containing 20% (w/w) of Hydroxy Propyl-β-Cyclodextrin gave superior OXC release of 85.50 ± 1.62% at the end of 12hours and fulfils the regulatory requirement. The dissolution data was also evaluated for drug release kinetics and mechanisms.
Keywords: Oxcarbazepine, matrix tablets, cellulose ether polymers, fillers and solubilizing agents.